Establishing an Anthropogenic Nitrogen Baseline Using Native American Shell Middens - Oczkowski, Autumn; Gumbley, Thomas; Carter, Bobbi; Carmichael, Ruth; Humphries, Austin (Frontiers in Marine Science, 2016)
Narragansett Bay, Rhode Island, has been heavily influenced by anthropogenic nutrients for more than 200 years. Recent efforts to improve water quality have cut sewage nitrogen (N) loads to this point source estuary by more than half. Given that the bay has been heavily fertilized for longer than monitoring programs have been in place, we sought additional insight into how N dynamics in the system have historically changed. To do this, we measured the N stable isotope (δ15N) values in clam shells from as early as 3000 BP to the present. Samples from Native American middens were compared with those collected locally from museums, an archaeological company, and graduate student thesis projects, during a range of time periods. Overall, δ15N values in clam shells from Narragansett Bay have increased significantly over time, reflecting known patterns of anthropogenic nutrient enrichment. Pre-colonization midden shell δ15N values were significantly lower than those post-European contact. While there were no statistical differences among shells dated from the late 15th Century to 2005, there was a significant difference between 2005 and 2015 shells, which we attribute to the higher δ15N values in the effluent associated with recent sewage treatment upgrades. In contrast, the δ15N values of shells from the southern Rhode Island coast remained constant through time; while influenced by human activities, these areas are not directly influenced by point-source sewage discharge. Overall, our results show that this isotope technique for measuring δ15N values in clam shells provides useful insight into how N dynamics in coastal ecosystems have changed during thousands of years, providing managers vital historical information when setting goals for N reduction.